2020
DOI: 10.7150/thno.48291
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of exosomes in craniofacial and dental applications

Abstract: Exosomes, a specific subgroup of extracellular vesicles that are secreted by cells, have been recognized as important mediators of intercellular communication. They participate in a diverse range of physiological and pathological processes. Given the capability of exosomes to carry molecular cargos and transfer bioactive components, exosome-based disease diagnosis and therapeutics have been extensively studied over the past few decades. Herein, we highlight the emerging applications of exosomes as biomarkers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 141 publications
0
22
0
Order By: Relevance
“…Loading Exos into a supporting scaffold can prevent them from being quickly removed from the wound area. Additionally, synergies between Exos and scaffolds have been found that effectively promote wound repair [ 56 , 57 ]. We have highlighted those studies that utilize Exos loaded in bioactive scaffolds to promote wound healing in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Loading Exos into a supporting scaffold can prevent them from being quickly removed from the wound area. Additionally, synergies between Exos and scaffolds have been found that effectively promote wound repair [ 56 , 57 ]. We have highlighted those studies that utilize Exos loaded in bioactive scaffolds to promote wound healing in Table 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes, important paracrine mediators, contain a broad spectrum of bioactive molecules derived from parental cells, including mRNAs, miRNAs and proteins. They can transfer important molecules to target cells and modulate cell functions [134,135]. Notably, DPSC-derived exosomes (DPSC-exos) can mimic the therapeutic benefits of parent cells while avoiding overt immune reactions and loss of stemness during expansion, storage, and transportation in vitro.…”
Section: Exosome-mediated Pulp Regenerationmentioning
confidence: 99%
“…These factors are mutually restrictive. For example, “the purity” of Ti‐EVs is technically sensitive, which likely affects the interpretation of results, and accounts for the poor concordance among the results of individual studies (Xing et al., 2020 ). Conversely, in some studies on biomarker discovery, there may not be strict requirements for purity if certain biomarkers can be detected repeatedly in EV solutions.…”
Section: Problems and Solutionsmentioning
confidence: 99%